Assessing the impacts of the Road Safety Remuneration System in Australia - Rex Deighton-Smith (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper discusses the application of Regulatory Impact Assessment (RIA) to the specific context of Australia's Road Safety Remuneration System and, in doing so, highlights two complementary lessons: first; that RIA can provide important information to policy makers, even where complexity and a lack of data prevent the completion of a full benefit/cost analysis and, second; that RIA can only be influential when adopted as part of a well-designed and fully functioning process, particularly where the policy environment is a politically charged one.
Keywords: 330; Verkehrssicherheit; Kosten-Nutzen-Analyse; Staatliche Einflussnahme; Australien